PENGARUH CITRA MEREK DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT. HARIAN WASPADA MEDAN - Mohd. Heikal (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Purchasing decisions is the end result of a thought and action in the purchase decision for use, wear, or consume a product or service to meet the needs and desires. The decision of purchase or use can be influenced by brand image and distribution. This study aimed to determine the effect of brand image and distribution on purchase decisions on PT. Harian Waspada Medan. The population in this study is that consumers use a shipping service PT. Harian Waspada Medan. Data collection techniques to study the documentation, interviews and questionnaires to 100 respondents with accidental sampling technique as well as to test the validity and reliability, data analysis techniques using classical assumption test, multiple linear regression, T-test, F-test, and the coefficient of determination ( R-Square). Classical assumption test results known that the normal data so that both are used for multiple linear regression, multiple linear regression Y = 11 563 + 0.580X1 + 0.427X2. Ttest brand image variables obtained t 5.274 1.984 Ttable, significant value 0.000 0.05, showed a significant influence between the variables of the brand image of the buying decision. Then the distribution of variables obtained tcount 3.670 1.985 ttable, significant value 0.001 0.05, indicating the significant influence of the variable distribution of purchase  decision. Ftest obtained Fcount 47.933 Ftabel amount 3,090 with significant value 0.000 0.05, that the brand image and distribution simultaneously together significantly with purchasing decisions. Coefficient of determination obtained 0.497 or 49.7% indicated that about 49.7% variable purchase decisions are influenced brand imageand distribution, the remaining 50.3% is influenced by other variables not examined.